IMPLEMENTASI PEMUTUSAN HUBUNGAN KERJA (PHK) TERHADAP PEKERJA STATUS PERJANJIAN KERJA WAKTU TERTENTU (PKWT) PADA PT X DI KOTA MALANG - Sudibyo Aji Narendra Buwana; Mario Septian Adi Putra (Kompetensi (Competence : Journal of Management Studies), 2015)
Termination of employment is a termination of employment caused by workers, employers or both of them for a certain thing and resulted in the expiration of rights and obligations between workers and employee. In this journall discussed about the implementation of termination employee in PT Xwhich is a distribution company production facilities in Malang. The formulation of the problem is why the workers approved the Employment Agreement Specific Time (PKWT) orally at PT X and how the implementation of labor laws in force in Indonesia to resolve the problem Termination (PHK) which occurred in PT X. The research method in this study was using empirical juridical approach. Type and sources of data used in the primary data collection and secondary data, and analysis process was using descriptive qualitative. The efforts made by workers to obtain the rights that workers should be able to it in accordance with Law of Indonesia number 2 of 2004 on Industrial Relations Dispute Settlement and Law of Indonesia number 13 of 2003 on Manpower.